Analisis Perubahan Struktur Ekonomi Dan Sektor Unggulan Kota Kendari Tahun 2010-2020 - Puspitaningsih, Andriani; Djauhar, Asri; Permana, Teguh (Jayapangus Press, 2021)
This study aims to determine changes in the structure and leading sectors in the City of Kendari. This research is a quantitative research using secondary data from BPS in the form of GRDP of Kendari city based on the business field in 2010-2020. The results showed that the economic structure of the city of Kendari is dominated by the retail wholesale trade sector and the construction sector. Where in 2010 the trade sector gave the largest contribution to GRDP, but in 2020 the construction sector dominates the contribution to GRDP. The results of other studies show that the leading sector in the city of Kendari is the corporate services sector from 2010-2020. The implication of the results of this study is that the city of Kendari as a service city needs to make changes to urban planning related to trade. And as a city that has advantages in the service sector, it is necessary to issue policies that support service improvement in order to increase the value of the contribution of the service sector in the city of Kendari considering that the city of Kendari is not superior in terms of agriculture.